Environmental education as the urban afforestation method favoring the city of Itapira-SP - Martelli, Anderson (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Currently, concern for the environmentis presentin the lives ofmost of the population. The affection, understanding andresponsibilityare essentialvaluesin a process thatdepends on cooperation andvirtuesarenecessaryto combatour paradigmsand prejudiceswhen we portrayurban forestry. This articleportraystheenvironmental educationdevelopedby the Department ofAgriculture andthe Environmentin October2014in celebrationof Children’s Daywith the distribution ofseeds, plantingguidelinesand donationsof seedlingsaimed at increasingurban greeningthe cityItapira-SP. Despite its importance,the subjectisrarely discussedand studied,especiallyin academia.The results showedthat the activitiesin this studycharacterizeplausibleactionswith regardto theawareness of childrenand familieson issuesrelatingto urban areasserving as a linkto participatein the constructionof cities andpreservation ofexistingtreesin this space.